PASAR DI SUDUT TIGA KORIDOR LAMA SEMARANG SEBAGAI PEMBENTUK PLACE DAN LINGKAGE EKONOMI - Siti Rukayah; Bambang Supriadi (Diponegoro University, 2017)
Semarang city has golden triangle corridor as a commercial corridor in the present day. But, in the past, the city had three corridors (bigger than now). There were Bodjong street (now known as Pemuda street, part of Groote Postweg 1809-1811), Mataram street (now Mt. Haryono road - the road that connects the old Semarang port to the Mataram kingdom in inland Java) and Veteran road (the road linking the western side of the city to the street Mataram, to avoid the downtown area which was a swamp area). There were traditional markets in each part of the node of triangle corridors (Johar, Randu Sari and Peterongan ) that still exist until now. This study aims to reveal the organization of city structure at that time. By using the historical method and a naturalistic approach were found that the formation of triangle corridor has a function as economic lingkage and economics place, connecting and attracting each other. In the city development, these markets become magnet and strategic node as a place for economic activity. It was formed by the existence of markets, functioning as the magnet for circulations dan be a place for the community. The existence of traditional villages along the corridors which have toponyms based on community economic activity at that time, became evident that the economic linkage has been formed in the past. This phenomenon has become a new knowledge that can be applied to the government for creating the concept of a city walk/ shopping belt corridor based on local wisdom of the urban planning in the past. Recommendations of this study is to preserve and develop the urban design in the past, so it can be utilized in the present situation.